A novel SLC2A1 mutation linking hemiplegic migraine with alternating hemiplegia of childhood. (January 2015) - Weller, Claudia M; Leen, Wilhelmina G; Neville, Brian GR; Duncan, John S; Vries, Boukje de; Geilenkirchen, Marije A; Haan, Joost; Kamsteeg, Erik-Jan; Ferrari, Michel D; Maagdenberg, Arn MJM van den; Willemsen, Michèl AAP; Scheffer, Hans; et al.
Background: Hemiplegic migraine (HM) and alternating hemiplegia of childhood (AHC) are rare episodic neurological brain disorders with partial clinical and genetic overlap. Recently, ATP1A3 mutations were shown to account for the majority of AHC patients. In addition, a mutation in the SLC2A1 gene was reported in a patient with atypical AHC. We therefore investigated whether mutations in these genes may also be involved in HM. Furthermore, we studied the role of SLC2A1 mutations in a small set of AHC patients without ATP1A3 mutations. Methods: We screened 42 HM patients (21 familial and 21 sporadic patients) for ATP1A3 and SLC2A1 mutations. In addition, four typical AHC patients and one atypical patient with overlapping symptoms of both disorders were screened for SLC2A1 mutations. Results: A pathogenic de novo SLC2A1 mutation (p.Gly18Arg) was found in the atypical patient with overlapping symptoms of AHC and hemiplegic migraine. No mutations were found in the HM and the other AHC patients. Conclusion: Screening for a mutation in the SLC2A1 gene should be considered in patients with a complex phenotype with overlapping symptoms of hemiplegic migraine and AHC.